Seleka’s profane potency: Kava artists and rebellious music in Tonga - Tecun , Arcia; Petelo, Taniela (Perfect Beat, 2021)
The Seleka art and kava collective is found in the heart of the Kingdom of Tonga’s urban centre and capital. Seleka is a transformed nickname which is a play on the word kasele, meaning toilet or outhouse, an external othering and internal acceptance of divergence within Tongan society. Seleka is a site where urban Tongans paint and drink kava together while listening to rebellious music, incorporating some of the aesthetics and politics of these musical genres into their group. They have a broader musical playlist than most kava clubs in Tonga, which includes punk, rock and metal. This article explores the character of Seleka as a radical critique to Western introduced social constructs such as puritan respectability, which have become part of Tonga’s modern cultural norms. Seleka performs and generates mana (potency/prestige) through noa (profanity/neutralization) by desecrating the ‘sacred’ and recreating a new alternative. This act of rebellion is presented as a contemporary manifestation of an ancient Tongan practice where the ‘profane’ was used to identify and bring balance to the most tapu (‘sacred’/protected).